Hypothesis: Why PDE Inhibitors should be Examined in Treatment of Creutzfeldt-Jakob and Prion Diseases - Gelbard, Amos (British Journal of Healthcare and Medical Research, 2025)
cGMP and cAMP are both cyclic nucleotides that act as second messengers in intracellular signaling pathways. Both cGMP and cAMP have been found to be significantly depleted in Creutzfeldt-Jakob disease (CJD). The way to recover cGMP and cAMP levels is through Phosphodiesterase (PDE) inhibitors that some of them, like Viagra, are currently in treatment for Erectile Dysfunction. Therefore it's possible to hypothesize that PDE inhibitors may have a role in CJD treatment, which should be examined further.